(untitled) (KULT_online, 2017)
With the anthology Memory in Ancient Rome and Early Christianity Karl Galinski and his fellow contributors aim to give an introduction into the application of the field of “memory studies” in the ancient studies. In addition, they want to encourage further discussions. In order to do so they have collected 13 case studies under five main topics. Central fields of investigation are the role of memoria in the literature of the roman empire, the interrelation between emperor and memory, the interdependence between visual culture and memoria, and the role of memory in roman religion and early Christianity. In addition there is an essay from a neuropsychological perspective.